FAKTOR – FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN DI JALAN SEA KELURAHAN MALALAYANG SATU BARAT KECAMATAN MALALAYANG KOTA MANADO (Factors Affecting the Land Conversion on Sea Road, Malalayang Satu Barat Village, Malalayang Sub District, Manado City) - Meidyta A. R. Pinontoan; Oktavianus Porajouw; Mex L. Sondakh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
Land is one of the main elements in supporting human life. The high domestic need is one reason for farmers to change the function of their land. The objective of this research is to identify and describe the factors that affect land use change in Jalan Sea, Malalayang, Satu Barat Village, Malalayang Sub District, Manado City. The study was conducted from July to September 2020. The sampling method used was simple random sampling method. This study uses secondary data obtained from the Malalayang Satu Barat Village Office. For primary data obtained from direct interviews with land owners. The data is then analyzed using tables and described descriptively. The research results showed that the factors causing the land conversion on Sea Street, Malalayang Satu Barat Village Malalayang Sub District Manado City were sending children to school, marrying off children, high selling prices offered by buyers, pressure to meet family needs, and no one taking care of the land. Of the five factors, the most dominant factor is sending children to school.Keywords: Land Conversion, Sea Road, Malalayang Satu Barat Village